Family caregivers in primary care: a survey of German general practitioners on procedures and problems experienced in day-to-day practice - Julian Wangler; Michael Jansky (Springer, 2023)
Abstract Background By providing both assistance and support, GPs can play a central role for family caregivers. By catering to the needs of caregivers, they are capable of stabilising in-home care settings over the long term. The aim of the present study is to provide a status quo analysis of how GPs assess their options for supporting individuals providing care, as well as the focal points set by their practice, and their estimation of obstacles and challenges encountered in day-to-day practice. Method An online questionnaire was used to survey a total of 5112 GPs in North Rhine-Westphalia between April and November 2022 (response quota: 46%). A heterogeneous random sample was obtained (58% male, 42% female; average age: 57; 50% medium-sized town/city practice, 50% rural/small town practice). To determine significant differences between two groups, a t-test was used with independent random samples. Answers to free-form questions were analysed using a subsequent coding based on a qualitative content analysis. Findings A total of 70% of respondents have frequent contact with family caregivers. Some 79% consider GPs to be well-suited to the role of primary contact point for caregivers and coordinating care. GP-carer support relationships typically arise as a result of caregivers approaching GPs (90%). Topics frequently addressed involve a worsening of the care situation (77%) and changes in the care needed (86%); consultations in the initial phase of the care situation are less common (44%). While respondents perceive a complex constellation of needs on the part of family caregivers, differences in priorities are observable between GPs in urban and rural environments (involvement of consultant/support network versus proactive and psychosocial assistance). GPs experience a wide range of challenges in providing assistance to caregivers, including the timely organisation of appropriate relief programmes (87%), referring caregivers to suitable help services (80%) or the early identification of informal caregivers (60%). Discussion In order to strengthen the GP role, the practice team should talk to caregivers as early as possible, and refer them to suitable help and support programmes. To achieve effective support for successful care, it is important to cater equally to the needs of the persons giving and receiving care as part of the caregiver-care receiver-GP triad.